Experiences, mental well‐being and community‐based care needs of fathers of late preterm infants: A mixed‐methods pilot study - Shahirose Sadrudin Premji; Sandra Reilly; Genevieve Currie; Aliyah Dosani; Lynnette May Oliver; Abhay K. Lodha; Marilyn Young; Marc Hall; Tyler Williamson (Wiley, 2020)
Abstract Aims We explore fathers' experience of caring for a late preterm infant including their stressors, needs and corresponding interventions proffered by public health nurses. Design Pilot mixed‐methods exploratory sequential design. Methods We collected (a) qualitative data from semi‐structured interviews (N = 5) and (b) quantitative data (N = 31) about fathers' levels of stress (Parenting Stress Index), anxiety (Speilberger State-Trait Anxiety) and depression (Edinburgh Postnatal Depression Scale) at 6-8 weeks after birth of their infant. Results Fathers appreciated their infant was born 'early', however, discovered through experience the demands of their infant, which appeared as stress (child and parent domains) and anxiety. Themes: hypervigilance in care explained the fathers' sense of competency and role restriction; infant fatigue and parental feeding elucidated the stressful aspect of father-infant interaction. Unscientific advice from healthcare providers was confusing and frustrating while uncertainty of rehospitalization caused worries, fears or stress. One father experienced depressive symptoms.